Spiritualizing Holistic Education in the 21st Century: An Overview of Islamic and Western Perspectives - Rofhani, Rofhani; Yusuf, M.; YS, Arbaiyah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
This study examines the spiritualization of holistic education in the 21st century from Islamic and Western perspectives, highlighting the differences and similarities in spiritual paradigms that play a crucial role in shaping well-rounded individuals. The Islamic perspective emphasizes the values of tawhid, tazkiyah, and amanah, which lead to moral and ethical development. In contrast, the Western perspective focuses more on self-awareness, mindfulness, and social responsibility, promoting mental and emotional balance. Despite having different philosophical foundations, both perspectives contribute to the same educational goal: character formation and social awareness. This study also identifies the significance of the spiritual paradigm in addressing modern global challenges, such as mental health crises and social inequalities.